Potential of mean force and molecular dynamics study on the transient interactions between α and β synuclein that drive inhibition of α-synuclein aggregation. Issue 15 (18th November 2017) - Sanjeev, Airy; Sahu, Ravi Kumar; Mattaparthi, Venkata Satish Kumar
Abstract : Self-association of α-synuclein (αS) into pathogenic oligomeric species and subsequent formation of highly ordered amyloid fibrils is linked to the Parkinson's disease. So most of the recent studies are now focused on the development of potential therapeutic strategies against this debilitating disease. β-synuclein (βS), a presynaptic protein that co-localizes with αS has been recently reported to act as an inhibitor of αS self-assembly. But the specificity of molecular interaction, nature and location between αS/βS is not known despite the potential importance of βS as an inhibitor of αS. We used molecular dynamics and potential of mean force (PMF) to study association of αS/βS and αS/αS. The calculated PMF indicates that contact wells are significantly deeper and presence of a minimum at αS/βS separation of 13.5 Å with a free energy barrier of 40 kcal/mol. We observed the dissociation energy barrier to be two times higher for the hetero-dimer (αS/βS) than the homo-dimer (αS/αS). We also carried out umbrella samplings involving two degrees of freedom (one being the distance between the monomeric units and the other angle between the long axes of the two monomeric chains) and observed similar PMF profile. We noticed relatively stronger range of transient interactions between the monomeric units in hetero-dimer (αS/βS) than homo-dimer (αS/αS). So our findings suggest that αS readily combines with βS to form hetero-dimer than combining with itself in forming homo-dimer. Hence we see predominant transient interactions between αS and βS can be used to drive inhibition of αS aggregation.